2019
DOI: 10.14569/ijacsa.2019.0101101
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection using Unsupervised Methods: Credit Card Fraud Case Study

Abstract: The usage of credit card has increased dramatically due to a rapid development of credit cards. Consequently, credit card fraud and the loss to the credit card owners and credit cards companies have been increased dramatically. Credit card Supervised learning has been widely used to detect anomaly in credit card transaction records based on the assumption that the pattern of a fraud would depend on the past transaction. However, unsupervised learning does not ignore the fact that the fraudsters could change th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In the case of outlier and noisy data being indiscernible in datasets, several studies illustrated that by eliminating noisy and outlier data at the preprocessing step, the predictive models' performance is improved [32][33][34]. Xia (2019) [35] proposed integration between outlier removal and gradientboosting algorithm for credit scoring on peer-to-peer lending datasets.…”
Section: A Traditional Credit Scoring Modelsmentioning
confidence: 99%
“…In the case of outlier and noisy data being indiscernible in datasets, several studies illustrated that by eliminating noisy and outlier data at the preprocessing step, the predictive models' performance is improved [32][33][34]. Xia (2019) [35] proposed integration between outlier removal and gradientboosting algorithm for credit scoring on peer-to-peer lending datasets.…”
Section: A Traditional Credit Scoring Modelsmentioning
confidence: 99%
“…To solve these imbalanced dataset issues, the initial focus is to generate artificial fraudulent data that balances the overall data presented to the models for training. Although Random oversampling technique provides a decent starting point, its main drawback is the creation of smaller decision regions which may further contribute to the overfitting problem (7) . This observation leads to the use of oversampling methods that specifically generate synthetic data that aid this domain.…”
Section: Related Workmentioning
confidence: 99%
“…Autoencoder and MLP are both unsupervised algorithms. In (7) , three unsupervised models are used for anomaly detection, more specifically Credit Card Fraud -and it is shown that Autoencoder outperforms the other two models (One-Class SVM and robust Mahala Nobis). Autoencoder is the most commonly used unsupervised model for anomaly detection but it still falls short in performance when compared to the Multi-Layer Perceptron model.…”
Section: Introductionmentioning
confidence: 99%
“…After conducting n‐grams, the bag of words was used to break words into individual word counts variables. The machine learning algorithms have been used in all areas of day‐to‐day life, from anomaly detection, 21 and crash prediction, 22 to sentiment analysis of the investors 23 . The below sections discuss the machine learning techniques have been used for training and evaluation of model accuracy.…”
Section: Machine Learning Algorithmsmentioning
confidence: 99%